Correlation analysis of the achievements of the five-pillar community-based total sanitation program and its indicators with trends in diarrhea - Hardini, Zahra Tamamy Surya (Asian Journal of Toxicology, Environmental, and Occupational Health, 2026)
Background: Diarrhea is a public health problem that remains a serious concern worldwide, including in Indonesia. Diarrhea can affect all age groups, both children and adults, but toddlers are the most vulnerable to this disease due to children's immature immune systems and their dependence on parents for personal and environmental hygiene. According to data from the Semarang City Health Office in 2023, the number of diarrhea cases showed a fluctuating trend from 2016 to 2023. In 2018, there were 50,021 cases recorded, decreasing to 21,765 cases in 2021, but increasing again to 36,534 cases in 2023, where 29.1% were cases in toddlers. This data indicates that children are still the most vulnerable group to diarrheal disease. Method: This study used a comparative descriptive design with secondary data. The data collection technique uses data sources derived from the Semarang City Health Office profile which includes 5 community-based total sanitation Pillars (Pillar 1: SBS, Pillar 2: CTPS, Pillar 3: PAMMRT, Pillar 4: PSRT, Pillar 5: PLCRT) as well as additional indicators (PKURT and Access to Healthy Homes) from 37 Community Health Centers and 16 Districts. Data is presented as a percentage of households from a total of 552,978 households, while data on total and toddler diarrhea cases (2018–2023) are presented in the form of bar charts. Finding: The achievement of community-based total sanitation in Pillar 1 (Stop Open Defecation) has reached 100%. This is followed by Pillar 2 (CTPS) at 94.02%, Pillar 3 (PAMM-RT) at 92.97%, Pillar 4 (PSRT) at 89.08%, and the lowest, Pillar 5 (PLCRT) at 88.50%. Additional indicators on Access to Healthy Homes reached 91.79%, while Household Air Quality Management (PKURT) had the lowest achievement at 67.2%. In 2018, diarrhea cases peaked at 50,021, drastically decreased in 2021 to 21,765, and then toddler diarrhea cases reached an average of around 27% to 35% of the total cases. Conclusion: The community-based total sanitation achievement in Semarang City shows that pillar 1 (SBS) has successfully reached 100% and is followed by pillar 2 (CTPS) and pillar 5 (PLCRT) which stopped the potential for control in diarrhea cases (especially seen in the 2020-2021 period). However, there was an increase in diarrhea cases in 2022-2023 followed by behavior in pillar 4 (PSRT) and additional indicators  still being the weakest link in environmental-based disease prevention efforts. Novelty/Originality of this article: This research is a study that is still rarely conducted from previous research. This study includes the achievement of the five community-based total sanitation pillars and additional indicators with long-term diarrhea case trends starting from 2016–2023 and identifies the influence of behavioral and spatial factors (between health centers) on disease closure.